Creating successful new products: challenges for Indian industry - Krishnan, Rishikesha T.; Prabhu, Ganesh N. (1999)
Firms in emerging markets face unique problems in new product development such as limited purchasing power, high price sensitivity, limited design skills and experience, lack of qualified vendors and inappropriate engineering resources. This article discusses these problems and suggests questions for further research. - Reproduced
Keywords: India - Industries; Industrial development